Early intervention exercise training does not delay prostate cancer progression in Pten−/− mice. Issue 11 (10th June 2020) - Taylor, Renea A.; Farrelly, Simon G.; Clark, Ashlee K.; Watt, Matthew J.
Abstract: Background: There is convincing evidence that men with advanced prostate cancer experience improved quality of life as a result of exercise therapy, although there is limited preclinical, and no clinical, data to directly support the notion that exercise training improves prostate cancer prognosis or outcome. The aim of this study was to investigate the effect of regular exercise training on the early stages of prostate cancer progression, as well as assessing whether alterations to prostate cancer metabolism are induced by exercise. Methods: Mice with prostate‐specific deletion of Pten ( Pten −/− ) remained sedentary or underwent 6 weeks of endurance exercise training or high‐intensity exercise training involving treadmill running. At the conclusion of the training period, the prostate lobes were excised. A portion of fresh tissue was used to assess glucose, glutamine, and fatty acid metabolism by radiometric techniques and a second portion was fixed for histopathology. Results: Despite the implementation of an effective exercise regime, as confirmed by improvements in running capacity, neither prostate mass, cell proliferation or the incidence of high‐grade prostate intraepithelial hyperplasia or noninvasive carcinoma in situ were significantly different between groups. Similarly, neither glucose uptake, oxidation and de novo lipogenesis, glutamine oxidation, or fatty acid uptake, oxidation and storage into various lipids were significantly different in prostate tissue obtained from untrained and exercise trained mice. Conclusions: These results show that 6 weeks of moderate or high‐intensity exercise training does not alter substrate metabolism in the prostate or slow the progression of Pten ‐null prostate cancer. These results question whether exercise is a useful therapy to prevent or delay prostate cancer progression.